Efforts to Maintain the Health of Children with Special Needs (ABK) During the Pandemic through Online Education Seminars - Ziske Maritska (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Sudden changes that cover all aspects of life in a short time, such as what happened during the current COVID-19 pandemic, can pose challenges to not only the children with special needs, but also their parents / guardians. This community service activity is carried out in the form of online educational seminars on efforts to maintain the health of children with special needs during the pandemic for parents / guardians of children with special needs who attend SLB C Karya Ibu Palembang and also common populace. This activity aims to provide a better understanding to parents / guardians of children with special needs about what children with special needs may face and live with during the pandemic.